Influence of the Single Coronary Vessel on Acute Outcomes of In-Stent CTO Recanalization - Jan-Erik Guelker; Christian Blockhaus; Edward Kemala; Klaus Ingerfurth; Julian Kuervers; Alexander Bufe (Reviews in Cardiovascular Medicine, 2022)
Objective: Recanalization of in-stent chronic total occlusion (IS-CTO) is challenging and has resulted in inconsistent results. The aim of our study was to analyze the influence of the individual coronary vessels on the acute outcomes following IS-CTO PCI. Methods: This was an observational retrospective study, including 66 patients undergoing recanalization of a CTO. The CTO interventions were performed bi-femoral using 7-French guiding catheters. A composite endpoint summarizing severe complications was evaluated, including emergency coronary artery bypass grafting surgery (CABG) and cardiac death. Results: We subdivided our cohort into three groups (LAD group, LCX group, RCA group). The retrograde technique and the utilization of an extension catheter were used more frequently in patients with a RCA IS-CTO. There was no significant difference between the composite safety endpoints amongst the three groups. Technical success was independent of the involved vessel. Conclusions: Success and complication rates are independent of the occluded vessel. This challenging and complex coronary intervention is feasible and can be carried out in complete safety.